2011
DOI: 10.1016/j.ab.2011.01.014
|View full text |Cite
|
Sign up to set email alerts
|

An enzymatic fluorescent assay for the quantification of phosphite in a microtiter plate format

Abstract: A sensitive fluorometric assay for the quantification of phosphite has been developed. The assay uses the enzymatic oxidation of phosphite to phosphate by a recombinant phosphite dehydrogenase with NAD + as co-substrate to produce the highly fluorescent reaction product resorufin. The optimised assay can be carried out in a 96-well microtitre plate format for high-throughput screening purposes and has a detection limit of 0.25 nmol phosphite. We have used the method to quantify phosphite levels in plant tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Current evidence suggests that plants do not assimilate Ph i into organic compounds and that oxidation of Ph i to P i as occurs in microbes is unlikely (Carswell et al ., 1997; Danova-Alt et al ., 2008; Berkowitz et al ., 2011). However, this does not rule out the possibility that Ph i affects metabolism by mimicking P i , for example by competing for catalytic sites or in the allosteric regulation of enzymatic reactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Current evidence suggests that plants do not assimilate Ph i into organic compounds and that oxidation of Ph i to P i as occurs in microbes is unlikely (Carswell et al ., 1997; Danova-Alt et al ., 2008; Berkowitz et al ., 2011). However, this does not rule out the possibility that Ph i affects metabolism by mimicking P i , for example by competing for catalytic sites or in the allosteric regulation of enzymatic reactions.…”
Section: Resultsmentioning
confidence: 99%
“…After clearing the lysate by centrifugation at 14 000 g and 4 °C for 15min, the supernatant was assayed for phosphate and phosphite as described previously (Ames, 1966; Berkowitz et al ., 2011). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTDH with dual cofactor specificity has been fused to flavin monooxygenases and the resulting self-sufficient biocatalysts have excellent activities for enantioselective catalysis [6][9]. PTDH has also found use in fluorescence assays to quantify phosphite concentrations in plants [10].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, no signal of the PTXD protein was observed in the WT control, whereas in both CrB‐1 and CrP‐13 transgenic lines, the signals corresponding to PTXD were present (Figure b). We determined PTXD activity in several C. reinhardtii transgenic strains, using an optimized fluorometric protocol previously reported (Berkowitz et al ., ). We found that strains CrB‐1, CrP‐6, CrP‐13, CrX‐3 and CrX‐9 showed significant levels of PTXD activity, which correlated with their capability to metabolize Phi (Figure c).…”
Section: Resultsmentioning
confidence: 97%